Compensation of Electrical Voltage in Distribution System by Dynamic Voltage Restorer - Soe Soe Ei Aung; May Phone Thit (Department of Electrical Engineering ITS and FORTEI, 2019)
Electrical ac power systems consist of generation systems, transmission and distribution networks. The large three phase industrial loads at various distribution and transmission voltages as well as single-phase residential and commercial loads are supplied by the networks. Nowadays, the power quality such as voltage sags/swell, transient interrupts and harmonic distortions in sinusoidal waveforms are concerned with most of the electrical loads. The power quality problems such as voltage sags, swells and harmonics are caused by the widespread using of power electronics devices in power system. In this paper, electrical voltage sags/swells of power quality problems are considered because this problem is one of the most severe disturbances to the industrial equipment of distribution system. Thus, mitigation of these voltages in distribution system is necessary. So, series connected power electronics based device such as Dynamic Voltage Restorer (DVR) is chosen to compensate these voltage for mitigating quickly the voltage sag/swell in the system and restoring the load voltage to the nominal value. For case study, Myaungtagar industrial zone is chosen due to furnaces and large motor drives that cause the common problems such as voltage sag/swell in this system. In this paper, performance analysis of voltage sag/swell compensation of power distribution system with Dynamic Voltage Restorer (DVR) under various fault conditions is carried out. The proposed configuration model uses MATLAB/SIMULINK and the performance of voltage compensation and restoration of load voltage to the nominal value with DVR under various fault conditions is verified by the simulation results.Keywords: dynamic voltage restorer, voltage compensation, voltage sag, voltageswell.